1995
DOI: 10.1590/s0037-86821995000300010
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa participante na intervenção da transmissão de helmintoses intestinais (cidade satélite do Paranoá - Distrito Federal)

Abstract: This work was developed in the Paranoá city town of the Federal District of Brazil. It used techniques of participative research with the aim of reducing intestinal helminths transmission in a group of children at nutritional risk. The family nucleus, that is, parents, children and other relatives living together in the same house, was used as reference for this research. All steps of the work were followed simultaneously by technical and educative actions. The technical actions were related to faecal examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
7

Year Published

1998
1998
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
0
1
0
7
Order By: Relevance
“…Para esse fim, foram seguidas as orientações sinalizadas em trabalhos de PP e educação popular (Bortef, 1984;Brandão, 1984;Pontual, 1985;Laurell et al, 1992;Mello & Carmo, 1994;Mello et al, 1995). O conjunto dessas orientações apontou um processo avaliativo, considerando tanto os aspectos qualitativos da pesquisa, quanto os quantitativos.…”
Section: Avaliaçãounclassified
See 2 more Smart Citations
“…Para esse fim, foram seguidas as orientações sinalizadas em trabalhos de PP e educação popular (Bortef, 1984;Brandão, 1984;Pontual, 1985;Laurell et al, 1992;Mello & Carmo, 1994;Mello et al, 1995). O conjunto dessas orientações apontou um processo avaliativo, considerando tanto os aspectos qualitativos da pesquisa, quanto os quantitativos.…”
Section: Avaliaçãounclassified
“…O trabalho se desenvolveu através da pesquisa participante (PP), cuja abordagem processual de articulação de um conhecer e agir contribui diretamente para resolução de problemas de interesse coletivo (Bortef, 1984;Brandão, 1984;Gajardo, 1986;Demo, 1989;Corcega, 1992;Laurell et al, 1992;Abbott et al, 1993;Hollanda, 1993;Mello, 1994Mello, , 1996Mello et al 1995;Cornwall & Jewkes, 1995). De caráter dialético emancipatório, essa metodologia tem como princí-pio fundamental uma forma de participação onde todos -pesquisadores e população -são sujeitos de um mesmo processo de exercício de cidadania objetivando transformação social.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Nevertheless, the eradication of helminthiasis is still very difficult, due to many factors that determine this prevalence. The improvement of environmental conditions together with personal hygiene, direct care, and participating research would be capable of decreasing the rate of enterparasitosis incidence in the world 6,7 . Several studies conducted in different countries and populations revealed a varying rate of prevalence of enteroparasite infection from 14.6% to 91.0% [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…A escola é ponto de partida eficiente para a educação voltada à saúde pública, envolvendo diversas questões como, por exemplo, a dengue (Andrade, 1998), helmintíases (Mello et al, 1995;Santos et al, 1993) ou a pediculose, particularmente geral e muito freqüente no meio escolar (Madureira, 1992). As crianças, e especialmente as estudantes, formam classicamente um excelente canal para a introdução de novos conceitos na comunidade, pelo fato de serem membros permanentes desta, e por estarem com o cognitivo em formação.…”
Section: Introductionunclassified